2016
DOI: 10.3389/fpls.2016.01783
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Vitis vinifera Subtilase Gene Family: A Possible Role in Grapevine Resistance against Plasmopara viticola

Abstract: Subtilisin-like proteases, also known as subtilases, are a very diverse family of serine peptidases present in many organisms. In grapevine, there are hints of the involvement of subtilases in defense mechanisms, but their role is not yet understood. The first characterization of the subtilase gene family was performed in 2014. However, simultaneously, the grapevine genome was re-annotated and several sequences were re-annotated or retrieved. We have performed a re-characterization of this family in grapevine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…The first subtilase gene family to be described belonged to Lycopersicon esculentum (tomato) and consisted of 15 members (Meichtry et al ., ). After this work, subtilase gene families were also characterized in Arabidopsis thaliana , presenting 56 known genes (Rautengarten et al ., ), in Oryza sativa (rice) with 63 genes (Tripathi and Sowdhamini, ), in moss Physcomitrella patens with 23 genes, in Populus trichocarpa with 90 genes (Schaller et al ., ) and, more recently, in Vitis vinifera and Solanum tuberosum (potato), both with 82 known genes (Figueiredo et al ., ; Norero et al ., ).…”
Section: Subtilisin‐like Proteases: History Classification and Genermentioning
confidence: 97%
See 1 more Smart Citation
“…The first subtilase gene family to be described belonged to Lycopersicon esculentum (tomato) and consisted of 15 members (Meichtry et al ., ). After this work, subtilase gene families were also characterized in Arabidopsis thaliana , presenting 56 known genes (Rautengarten et al ., ), in Oryza sativa (rice) with 63 genes (Tripathi and Sowdhamini, ), in moss Physcomitrella patens with 23 genes, in Populus trichocarpa with 90 genes (Schaller et al ., ) and, more recently, in Vitis vinifera and Solanum tuberosum (potato), both with 82 known genes (Figueiredo et al ., ; Norero et al ., ).…”
Section: Subtilisin‐like Proteases: History Classification and Genermentioning
confidence: 97%
“…When comparing resistant and susceptible grapevine genotypes, a subtilase presenting sequence similarity with tomato P69C was observed to be constitutively expressed in the resistant genotypes, increasing its expression after inoculation (Figueiredo et al ., ; Monteiro et al ., ). More recently, subtilase participation in the defence response against P. viticola was reinforced (Figueiredo et al ., ). In Vitis pseudoreticulata leaves infected with E. necator , an up‐regulation of several subtilase genes was also reported (Weng et al ., ).…”
Section: Subtilases Involved In Plant Defencementioning
confidence: 97%
“…The two most distantly related enzymes, AtSBT6.1 and AtSBT6.2, are the orthologs of mammalian site‐1‐protease (S1P) and tripeptidyl peptidase II (TPP2), respectively, while all other family members in subgroups SBT1 to SBT5 appear to be plant‐specific. Large SBT gene families have also been identified in other plant species, comprising 63 pyrolysin genes in rice ( Oryza sativa ; Tripathi & Sowdhamini, ), 82 in grape ( Vitis vinifera ; Cao et al ., ; Figueiredo et al ., ), and 82 in potato ( Solanum tuberosum ; Norero et al ., ). As compared with the entire genome of Arabidopsis, 60% of which is contained in large duplicated segments, SBT family expansion has been driven predominantly by tandem gene duplications.…”
Section: Phylogeny Of Plant Sbts and Family Organizationmentioning
confidence: 99%
“…Since then, in Arabidopsis thaliana, 56 known genes of this family was found (Rautengarten et al 2005), and 63 genes of this family in Oryza sativa (rice) was also indicated (Tripathi & Sowdhamini 2006). Besides, in the years that followed, the SBT family genes were explored in Physcomitrella patens (23 gene members), Populus trichocarpa (90 gene members), Vitis vinifera (82 gene members) and Solanum tuberosum (82 gene members), respectively (Figueiredo et al 2016, Schaller et al 2012, Sigrid Norero et al 2016.…”
Section: Introductionmentioning
confidence: 99%